BERMAIN MENCARI IDE: Desain dan Implementasi Permainan dalam Pengembangan Ide Produk Wisata di Desa Wisata Tegal Loegood, Kabupaten Sleman, Provinsi Daerah Istimewa Yogyakarta - Hartono, Yudo; Baiquni, Muhammad; Murtiningsih, Siti; Maryono, Agus (Sekolah Tinggi Pariwisata Sahid Surakarta, 2026)
This study examines how games can assist tourism village organizers in developing ideas for tourism products and explores their experiences using games to promote innovation within their villages. Data collection was conducted through role-play interactions between the tourism village management community and the villagers of Sukorejo Village, also known as Tegal Loegood Tourism Village. The study revealed that implementing the Mechanics, Dynamics & Aesthetics (MDA) framework through games can support tourism village organizers in generating new tourism product ideas for their villages. This approach also encourages an open, relaxed, and participatory environment, promoting active engagement. However, some implementation challenges are technical, such as managing time and inserting tourism themes from the community into game modification. The research recommends utilizing games to drive innovation in villages, to strengthen engagement among tourism village organizers during decision-making, and to cultivate a sense of equality and freedom of expression across generations. Keywords games, tourism product, tourism village organizer, decision making